THE SUBJECT AND QUALITY THROUGH THE PRISM OF LANGUAGE - GRDZELYAN, ROUZAN (Bulletin of Yerevan University H: Russian Philology, 2019)
The article is devoted to the description of the objective and qualitative nature of the semantics of the word, the correlation of formal grammatical and semantic features of the word – the mutual influence of the grammatical semantics of the word and the characteristics of the subject as an object of the external world.